PREPARING SCHOOL STUDENTS IN THE FIELD OF PHYSICAL CULTURE AND SPORTS BEFORE ENTRY TO HIGHER EDUCATION - Kadirov Shohbozjon; Melikuziyev Azizjon (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
Training of qualified personnel is always one of the important tasks of the education sector. The high level of demand for the physical condition of schoolchildren implies the existence of an additional stage of preparation for entrance exams to higher educational institutions in the field of physical culture and sports. The modern practice of preparing schoolchildren for higher education has shown that selection as a component of the process of forming the student contingent is a special "filter" that helps to select a small number of young people suitable for study. The quality of the preparation of schoolchildren up to the higher education institution is determined by the success of their future studies and the stability of the formed student contingent.